produção de mudas de maracujazeiro amarelo submetidas à salinidade em solo com biofertilizante bovino - Mesquita, Francisco de Oliveira; Cavalcante, Lourival Ferreira; Pereira, Walter Esfrain; Rebequi, Alex Matheus; Neto, Antonio João de Lima [UNESP]; Nunes, Járisson Cavalcante (My University, 2012)
The experiment was conducted in a greenhouse from May 1 to July 31, 2008, in Areia county, Paraiba State, PB, Brazil, in order to evaluate the effects of irrigation water salinity on initial growth of the passionfruit seedlings in non-saline substrate with and without bovine biofertilizer. The treatments were distributed in a completely randomized design, with three replications and twelve plants per plots, in a factorial arrangement 5 × 2 × 2, corresponding the former to the levels of salinity in the irrigation water: 0.5; 1.0; 2.0; 3.0 and 4.0 dS m-1, in soils with and without bovine biofertilizer applied at two moments (25 and 65 days after seedling emergence). The growth of the seedlings and the soil electrical conductivity were evaluated at the end of the experiment. The biofertilizer was diluted in a low saline water at a 1:1 ratio and was applied once two days before sowing, corresponding to 10% of the substrates volume. The increase in water salinity inhibited the growth in height of plants, leaf area and root length, but always to a lesser extent in the treatments with bovine biofertilizer. The increase in electrical conductivity of the irrigation water elevated the soil salinity, independently of the addition of biofertilizer.
Effect of saline irrigation waters and bovine biofertilizer application on the production of yellow passionfruit seedling
Keywords: Organic input; Passiculture; Passiflora edulis f. flavicarpa deg.; Sodium chloride; biofertilizer; crop plant; crop production; crop yield; electrical conductivity; experimental study; fertilizer application; growth response; inhibition; irrigation; leaf area; salinity; seedling; sodium chloride; substrate; Brazil; Paraiba; Bovinae; Passiflora edulis; Passiflora edulis f. flavicarpa; Passiflora ligularis